2005
DOI: 10.1007/s10620-005-2967-0
|View full text |Cite
|
Sign up to set email alerts
|

An Elemental Diet Controls Inflammation in Indomethacin-Induced Small Bowel Disease in Rats: The Role of Low Dietary Fat and the Elimination of Dietary Proteins

Abstract: Elemental diets (EDs) are effective in treating Crohn's disease. We hypothesize that low dietary fat and amino acids used as the sole nitrogen source are the major contributors for the success of EDs. We examined the influences of the addition of dietary fat and protein to an ED using an indomethacin-induced inflammation model in rat small intestine. In the ED-fed rats, the intestinal damage score was decreased compared with that in the standard chow group with decreasing intestinal permeability. By supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…[13] demonstrated that a ten-fold reduction of 16S rDNA in stool. This decrease in GI microbiota correlated with reduced production of IL-17, a cytokine associated with specific types of bacteria [14], [15], [16], by intestinal CD4+ T cells. Our antibiotic treatment reduced the number of bacterial 16S rDNA copies detected in stool by over 100-fold after two weeks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[13] demonstrated that a ten-fold reduction of 16S rDNA in stool. This decrease in GI microbiota correlated with reduced production of IL-17, a cytokine associated with specific types of bacteria [14], [15], [16], by intestinal CD4+ T cells. Our antibiotic treatment reduced the number of bacterial 16S rDNA copies detected in stool by over 100-fold after two weeks.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to bacterial-derived antigens, food antigens have also been implicated in the pathogenesis of IBD [11]. Supporting this, food restriction diets have been shown to improve IBD symptoms in human patients and in animal models [12], [13], [14].…”
Section: Discussionmentioning
confidence: 94%
“…Macroscopic intestinal damage was assessed by scoring four items (Table 1) as described by Chen et al (25). Intestinal permeability was assessed by measuring urinary excretion of phenolsulfonphthalein (PSP) after oral administration of 20 mg PSP (19,26) via a gastric tube. Urine was collected over the next 24 h, brought to 50 mL with distilled water, and centrifuged at 2,100 3g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Administration of indomethacin (Indo), a nonste-roidal anti-inflammatory drug, to experimental animals induces intestinal ulcers similar to those seen in CD patients (16,17). Previous work has demonstrated that an elemental diet (ED) can significantly reduce such Indo-induced intestinal damage (18,19). An ED contains free amino acids as a nitrogen source and is low in fat; thus, it can be readily absorbed without the need for digestion (20).…”
mentioning
confidence: 99%